Oral hygiene and dietary choices of 8-11year-old children with respect to the evidence-based oral health messages (diet and tooth brushing) in 3rd and 4th class children in primary schools in cork, Ireland, and their relationship to BMI taking account - Mohamed, Ahmed; Mairead Harding, Dr.; Janas Harrington, Dr. (International Journal of Dental Research, 2021)
Background: Dental caries and obesity are growing public health conditions over the word. Objective: The aim of this study was to determine the prevalence of being overweight and obese amongst 8-11-year-old children in Cork city and county, and whether there is an association with oral hygiene practices, dietary choices, and BMI.Methods: This is a cross-sectional analysis using secondary data. Data came from the Cork Childrenâ€™s Lifestyle Study (CCLaS); were analysed using logistic regression and controlling for potential confounder for 1061 children aged 8-11 years.Result: This study included 1,061 children, 58% of the sample were boys at median age 9 years (8-11 years). There was an association between BMI and toothbrushing (P >0.005). The relationship between BMI and diet frequency (breakfast, dinner meals and favorite snack) was statistically significant. Regarding diet quality, Junk food was only found statistically significant associated with BMI. While the relationship between BMI and diet quantity, several variables were found statistically significant associated with BMI include (Sum) Kcal-all-foods, total sugar from all include all beverages per day, and fibreaoac.Conclusion: The data from CCLaS suggested that the negative association between BMI and toothbrushing frequency in children aged 8 to 11 years-old requires further study. Dietary choices, especially sweets have an important role in being overweight and suffering obesity as indicated in this study and sugars are the principle etiological cause of dental caries. Therefore, strategies should be developed on a multidisciplinary level with a common risk factor approach.Â Â